Machine learning methods to predict the crystallization propensity of small organic molecules - Pereira, Florbela (2022)
Fundacao para a Ciencia e Tecnologia (FCT) Portugal, under grant UID/QUI/50006/2019 (provided to the Associate Laboratory for Green Chemistry LAQV) is greatly appreciated. Florbela Pereira thanks Fundacao para a Ciencia e a Tecnologia, MCTES, for the Norma transitoria DL 57/2016 Program Contract.